Questionable Industry-Sponsored Postneonatal Pediatric Studies in Slovenia - Klaus Rose, MD, MS; David Neubauer, MD; Jane M. Grant-Kels, MD (Elsevier, 2019)
ABSTRACT: Background: US and EU pediatric laws promote industry-sponsored pediatric studies, based on the therapeutic orphans concept that claims discrimination of children in drug treatment and drug development. Objective: We investigated the medical validity of international pediatric studies with centers in Slovenia, an EU member state, and challenge their medical utility. Methods: We analyzed international industry-sponsored pediatric studies with centers in Slovenia, listed in www.ClinicalTrials.gov, for their medical value. Results: Most pediatric studies triggered by the US Food and Drug Administration and by the European Medicines Agency were/are without medical or scientific value. They were/are formally and regulatorily justified, but lack medical sense and thus were/are unethical. Several even harm children and/or adolescents with serious diseases by exposing them to placebo or substandard treatment. Conclusions: Pediatric studies triggered by US and EU regulatory demands are a serious abuse of nonneonatal children and adolescents in Slovenia and worldwide. They are medically redundant at best and often deter patients from effective innovative personalized therapy. They also exclude young patients from reasonable studies. Institutional review boards/ethics committees should be alerted, should critically review all ongoing pediatric studies, should suspend those found to be questionable, and should reject newly submitted questionable ones. Key words: Pediatric clinical pharmacology, Pediatric drug development, Pediatric investigation plan, Pediatric laws, Pediatric legislation